Micro Learning for Undergraduate Students’ Writing Ability: An Effect on Writing English Text - Desna Fauziah; Erna Nawir; Susi Susanti; Robeeyah Bueraheng; Wahyu Ridhoni; Wenny Elsara (Lectura : Jurnal Pendidikan, 2023)
One of the factors that generate lack of students’ writing competence is the teaching methods used by the lecturer which is less desirable by the students. Micro learning comes as one of the alternatives to deliver the knowledge to the students which became the focus of this study on seeing the significance of the strategy in improving students’ ability to write English text. This is an experimental research involving 64 participants which was done in Universitas Muhammadiyah Sumatera Barat (UM Sumbar). The population of this study consisted of 124 students distributed across 4 classes. The sample selection was done using cluster random sampling, which resulted in one class being assigned as the experimental group and another class as the control group The data was gained by determining whether students have improved their writing scores (through writing rubric) by implementing micro teaching through pre-test and post-test. The researchers look for the statistical t-value with a significance level of <0.05. Furthermore, the researchers conduct further analysis through descriptive analysis using SPSS 24. The results of this research were obtained through a t-test with a significance level of 5% (0.05), yielding an observed t-value of 2.975, while the critical t-value was 2.306. These findings indicate that students' achievement in writing texts improved. Therefore, it can be concluded that micro-learning is an effective instructional method for enhancing the writing skills of English Education students at Universitas Muhammadiyah Sumatera Barat.